Caribbean diplomacy - Ramphal, Sir Shridath ([CCS] [Georgetown]GY, 2009)
Highlights the importance of the right choice of diplomats and the need for the capacity of the Foreign Ministry to support them and to service the government at home. Notes that the Caribbean needs to be active and effective in very many areas of foreign policy as an adjunct to its national and regional policies.